Longitudinal Responses to Weighing and Bathing Procedures in Preterm Infants. - Bembich, Stefano; Fiani, Giulia; Strajn, Tamara; Sanesi, Cecilia; Demarini, Sergio; Sanson, Gianfranco (J Perinat Neonatal Nurs, 2017)
Knowledge of the effects of nursing-induced stress on short-term outcomes in preterm infants is limited. Effects of 2 standard nursing procedures-weighing and bathing-on autonomic and motor stability of preterm infants were studied during their hospitalization. Outcomes were evaluated during and after the procedures. Eleven preterm infants were observed between 32 and 35 weeks' postmenstrual age (PMA) (postnatal days range: 4-63). Neonatal responses were assessed according to the Synactive Theory of Development and nursing was performed taking into account Newborn Individualized Developmental Care and Assessment Program (NIDCAP) principles. Effects of the studied nursing procedures on infants' stability during and after their execution were evaluated by nonparametric statistics. During monitored procedures, stress responses in autonomic and motor systems were observed at all PMAs. However, after 32 weeks' PMA, preterm infants also showed an autonomic and motor stability recovery 5 minutes after procedure completion. Contrary to our hypothesis, preterm infants showed to be stressed by weighing and bathing procedures up to 35 weeks' PMA. However, if facilitated and supported after nursing conclusion by interventions such as swaddling and nesting, according to NIDCAP principles, they recovered autonomic and motor stability by 5 minutes after ending procedures.
Keywords: Baths; Body Weight; Female; Humans; Infant Behavior; Infant Care; Infant, Newborn; Infant, Premature; Male; Neonatal Nursing